حكم الإجهاض وعقوبته عند المذاهب الأربعة والقرار الحكوميرقم 61 عام 2014 =Hukmu Al-Ijhaadh Wa 'Uquubatiji 'Nda Al Madzaahib Al Arba'ah Wa Al-Qaraari Al Hukuumy raqm 61 'Aam 2014 - Ma'shum, Qodim; , Dr. M. Muinudinillah Basri, M.A; , Dr. M. Abdul Khaliq Hasan, M.A., M.Ed (2015)
Abortion is expel the fetus before birth time intentionally the causes death. This is the crime of murder in the human. Nowdays, abortion is becoming one of the problems that endanger see increasing cases of abortion in Indonesia reached 15 per year for various reasons, and variety of them is the continuation of the pregnancy threatens the mother's life, or sophistication of medical technology in the fetus can be detected before is its birth with great accuracy, that the fetus will be born with a disease or congenital defects. In this case whether an abortion? How to legal abortion and the sanctions by 4 Madzhabs and Government Regulation 61 of 2014? What are the similarities and differences between the two. This type of discussion is the literature where there authors takes referrals from the data library data, the method of data collection related to this discussion, and then analyze the data analysis method of data inference and comparison of data. Discussion of the results: 4 Madzhabs different about opinion law before Allah blows the soul to the bodies, among them there is nothing of prohibiting and allowing. They agreed to ban abortions after spirit is blown to the body and also penalties for abortions is ghurrah (freed slave male or female). Meanwhile, according to Government Regulation 61 of 2014, abortions may be performed for two conditions, namely existence of the medical emergency and pregnant due to rape, while the sanction of abortion is imprisonment and fines. 4 Madzhabs an Government Regulation 61 of 2014 agreed with origin law of abortion is prohibited and permitted in emergencies, but they differ on the permissibility of abortion gestational age and sanction of abortion itself. According to the authors, abortion may be performed before and after this spirit in blown. If only there is a medical emergency such as the continuation of the pregnancy threatens the life of the mother or fetus as indicated by hereditary or congenital defect that can not be cured.